Mindfulness, Emotional Intelligence, and Gender as Predictors of Academic Motivation in High School Students - Askara, Ghanisa Anggit; Putra, Rahman Pranovri; Herwin, Herwin; Rizky, Deo Alfa (International Journal of Islamic Educational Psychology, 2024)
Academic motivation plays a very important role in the student's learning process, influencing various aspects of development. This study aims to see academic motivation in students in terms of mindfulness, emotional intelligence, and gender. This study is a quantitative study with an ex-post facto approach using multiple linear regression tests and using independent sample T tests to compare academic motivation based on gender. The number of samples in the study was 375 high school students using simple random sampling techniques. The results of this study indicate that there is a significant positive influence between mindfulness and emotional intelligence on academic motivation with a significance value of .000 (<.05) and affects academic motivation by 69.0%. Comparison of academic motivation based on gender found that men are higher than women with a mean difference of 1.78 with a significance of .004 which shows a significant difference.  This study shows that mindfulness and emotional intelligence are significant predictors of academic motivation in high school students. Mindfulness allows students to be more focused and aware of the learning process, thus reducing distractions and increasing academic engagement. Meanwhile, emotional intelligence helps students manage emotions, deal with academic stress, and build positive relationships, which in turn support motivation to learn.